Correction: Ahmed, H.; Ahmed, R. A Mass-In-Mass Metamaterial Design for Harvesting Energy at a Broadband Frequency Range. Energies 2023, 16, 5883 - Hossain Ahmed; Riaz Ahmed (Energies)
In the original publication [...]